Antibacterial Activity of Electrospun Silver Nitrate /Nylon 6 Polymeric Nanofiber Water Filtration Mats - Jabur, Akram Raheem; Abbas, Laith Kais; Moosa, Saja Aqeel (Al-Khwarizmi Engineering Journal, 2017)
Bacterial water pollution is a genuine general wellbeing concern since it causes various maladies. Antimicrobial nanofibers can be integrated by incorporating nanobiocides, for example, silver nanoparticles into nanofibers. Nylon 6 was dissolved in formic acid at a concentration of (25 wt. %) and tough antibacterial (AgNO3/Nylon) nanofibers were produced utilizing electrospinning system. Polymer solution was tested before accomplishing electrospinning process to acquire its surface tension, electric conductivity and viscosity, where every one of those parameters increased relatively with increasing concentration of (AgNO3) additions. SEM and EDX spectra were utilized to focus on the morphology, surface elemental membrane, fibers and porosize diameters. The resulted nanofiber membrane has an average fiber diameter of 139 nm for pure nylon 6 and 247 nm for (1.2 wt. % AgNO3/Nylon). The resultant polymer membrane was then tested for their ability to destroy microorganisms in water; antimicrobial tests showed that the prepared nanofibers have a high bactericidal effect against Escherichia Coli Bacteria with inhibition zone (10 mm) and antibacterial activity (99%). Likewise, these results highlight the potential utilization of these nanofibrous mats as antimicrobial agents.